The Effect of The Drill Method of Swimming Bracelet on Peak Expiratory Flow Rate In Asthma Patients - Akhmad Sobarna; Sumbara Hambali; Dodi Ilham; Rony Mohamad Rizal; Sherina Salsabila Arthamevia (Journal of Educational Science and Technology (EST), 2021)
This study aims to determine the effect of the breaststroke swimming drill method on the peak expiratory flow rate in asthmatics. This study uses an experimental research method with a one-group pre-test-post-test design, which means that research activities are carried out by giving an initial test before treatment and a final test after treatment. The subject of the study was an asthmatic patient aged 12 years using the purposive sampling technique. In this study, the research instrument used was a test to determine whether or not the effect of the breaststroke swimming drill method on the peak expiratory flow rate in asthmatics. The data analysis technique used in this study is to find the average value and standard deviation, test for normality using the Kolmogorov-Smirnov test, Marginal homogeneity test, and hypothesis testing using Paired T-test. This study indicates a significant result of an increase in the peak expiratory flow rate through the application of the breaststroke swimming drill method in someone with asthma.